STRATEGIC TERRITORIAL INTELLIGENCE FOR FAMILY FARMING IN THE CUIABÁ RIVER VALLEY AND SURROUNDINGS - Daltio, Jaudete; Gürtler, Salete; Alves Magalhães, Lucíola; Rodrigo Farias, André; Fernando Fonseca, Marcelo; Luís Ferraz da Silveira, Hilton; Roberto Rodrigues Martinho, Paulo; Alberto de Carvalho, Carlos; Mingoti, Rafael; Tomaz Ramos, Fabrício (Ra’e Ga: o Espaço Geográfico em Análise, 2025)
Family farming is a cornerstone of Brazil’s economic and social structure. It accounts for a significant portion of the national food production and plays a crucial role in promoting food security in the country. In the Metropolitan Region of the Cuiabá River Valley and Surroundings, this segment encompasses approximately 28,000 families residing in rural areas, organized into 10,547 agricultural establishments. The strengthening of family farming depends on its support by public policies which are capable of understanding regional specificities and creating effective mechanisms for the development and consolidation of the sector. In this context, a partnership was established between the Mato Grosso Company of Rural Research, Assistance, and Extension (EMPAER) and Embrapa, to develop a digital platform that integrates data across different territorial dimensions, aiming to characterize the region and, above all, provide analytical tools to support public policy and local investment decisions. This solution was based on the strategic territorial intelligence concept, which thematically organizes spatial data into five major frameworks: natural, agrarian, agricultural, infrastructural, and socioeconomic. We expect the platform to support territorial management efforts by public and private organizations by classifying the region’s municipalities according to their environmental and production potential. This, in turn, will assist research institutions and organizations responsible for rural planning, management, and technical assistance.